Equity in Social Emotional Learning Programs: A Content Analysis of Equitable Practices in PreK-5 SEL Programs - Ramirez, Thelma; Brush, Katharine; Raisch, Natasha; Bailey, Rebecca; Jones, Stephanie M. (Frontiers in Education, 2021)
As the positive impact of social emotional learning (SEL) has become widely recognized, there is increasing demand for SEL programs to address the diverse cultures, identities, and experiences of all students in the classroom, in particular students of color and other youth impacted by structural inequality. SEL programs increasingly provide resources and guidance to ensure that diverse students are represented in materials and content and to help educators understand how culture plays a role in the development and expression of SEL competencies. However, few programs are intentionally designed with equity in mind and even fewer examine how historical and structural inequalities impact both the teaching and learning of SEL skills. While many believe that SEL is well-positioned to play a role in creating learning environments where students of all cultures, races, identities, and backgrounds feel safe, respected, and empowered, the link between equity and SEL is not always clear. Furthermore, despite existing well-established, research-grounded practices from which to draw in other fields, the field of SEL currently lacks a coherent and unified definition of what constitutes equitable SEL and what equitable SEL looks like in the classroom. As schools and other educational settings strive toward creating more equitable learning environments for students, the field of SEL needs a clearer viewpoint and explicit practices describing how equity can be better integrated into SEL programming and practice. This paper describes the need for equitable SEL, summarizes existing research and practices, and provides a set of recommendations for implementing them effectively in schools and other educational settings. We begin with a brief exploration of the relationship between educational equity and SEL, describing the potential for SEL to create more equitable, inclusive, and just learning environments. Next, we present key perspectives from the literature that shape current views on how issues of equity can be integrated into SEL programming and practice, proposing a set of principles and definition for equitable SEL. Finally, we discuss the current state of PreK-5 SEL programs, using findings from a content analysis to describe the extent to which programs address equity in lessons and promote transformative SEL skill building.